2022
DOI: 10.1590/1980-5373-mr-2022-0118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Heat Input and Ageing Treatment on Microstructure and Mechanical Properties of AISI 317L Stainless Steel Dissimilar Welded Joints

Abstract: The present work investigated the influence of heat input and aging time on the microstructural characteristics and the mechanical properties of dissimilar AISI 317L austenitic stainless steel welded joints. The AWS ER2209 wire-electrode was used as filler metal, and two different heat input levels were applied (4 and 8 kJ/cm), aiming to verify the influence of this parameter on the deleterious phases precipitation. An aging heat treatment (AHT) was carried out at 700 °C for two different exposure times: 50 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
(51 reference statements)
1
1
0
Order By: Relevance
“…Various morphologies of austenite are observed: allotriomorphic austenite (γ A ), Widmanstätten austenite (γ W ), and idiomorphic austenite (γ I ). Their occurrence is consistent with literature reports for welds in grades 2209 [38,[45][46][47][48][49][50][51][52], 2101 [53,54], 2205 [55][56][57], 2507, and 2304 [55]. Observations regarding the occurrence of non-metallic inclusions are also consistent with literature reports [58][59][60] and result from the specificity of the manual metal arc welding process.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Various morphologies of austenite are observed: allotriomorphic austenite (γ A ), Widmanstätten austenite (γ W ), and idiomorphic austenite (γ I ). Their occurrence is consistent with literature reports for welds in grades 2209 [38,[45][46][47][48][49][50][51][52], 2101 [53,54], 2205 [55][56][57], 2507, and 2304 [55]. Observations regarding the occurrence of non-metallic inclusions are also consistent with literature reports [58][59][60] and result from the specificity of the manual metal arc welding process.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, a level was achieved that was very similar to that obtained in the research (Figure 10). Also, Antunes et al [47] showed that after annealing of grade 2209 welds at a temperature of 700 • C for 50 and 100 h (3000 and 6000 min), γ austenite and χ and σ phases appear in the microstructure. No δ ferrite was found.…”
Section: Discussionmentioning
confidence: 99%